Perceptions about Continuing Dental Education Program among Private Dental Practitioners in Davangere City, Karnataka, India - A Cross SectionalSurvey - Anjan Giriraju; Puja C Yavagal; Nagesh Lakshminarayan (Wolters Kluwer Medknow Publications, 2013)
Objectives: To assess perceptions of private dental practitioners regarding Continuing Dental Education (CDE) program in Davangere city. Materials & Method: A total of 104 private dental practitioners participated in the survey, of which 40 dentists were only private practitioners and 73 dentists were private practitioners as well as academicians. A closed ended questionnaire was administered to all the private dental practitioners of Davangere city. Results: All the private dental practitioners in the survey were aware about what is CDE program. Majority of the practitioners felt there is need to make attendance to CDE program compulsory and also renew the practice registration based on the credit point acquired by attending CDE program. Majority of practitioners preferred attending free and sponsored CDE programs and also felt attending CDE program kept them abreast with current knowledge enabling them to provide evidence based care. Majority of practitioners preferred to attend CDE programs related to clinical applications and recent advances provided through online and through workshops/hands on. Factors like cost, topic of the program and distance from home played major role in deciding the attendance of private dental practitioners to CDE program. Conclusions: Dental practitioners have positive attitude regarding CDE program. Practitioners opine CDE program can update their knowledge and enable them to provide evidence based care.